Analysis Of Patients' Opinion Of Prescribed Medicines: A Questionnaire - Based Pilot Study In Bulgaria - Zornitsa Emilova Mitkova; Miglena Doneva; Maria Dimitrova; Petya Nikolova; Konstantin Tachkov; Guenka Petrova (Polskie Towarzystwo Farmaceutyczne, 2023)
Evaluation of rational drug utilization (RDU) through WHO indicators is used to provide information about the level of development of national policy and to identify the necessity of further regulatory, patients or healthcare professionals -centered measures. The current study aims to investigatethe patients' perspective about medicines utilization by implementing the WHO's "followup" indicators in the Bulgarian practice. A prospective, cross -sectional, online inquiry study was conducted among Bulgarian population. The population above 18 years of age is 5.8 million of people and 400 people sample was considered sufficient with 95% CI. The study methodology is based on a modified version of the WHO "followup" indicators. The total number of answers was 467. The majority of patients aged over 56 years responded that they did not receive enough information about the side effects and interactions of the prescribed medicines and the most often they used the leaflet as a source of information. Most of the patients responded they always check the expiry date (61%), while 23 % of patients check it sometimes. In the group of patients over 65 years, 24% responded that they never check the expiry date. The results of our study suggest that rational medicines utilization is a broader concept depending on patients' knowledge and pharmacists and patients relation. It suggests that there is a need to educate both parties, mainly to increase health literacy and promote general aspects of rational medicines utilization.